The Application of Flow–Clutch States and AHP-QFD-FBS in the Design of Parent–Child Interaction Exercise Bikes - Na Li; Jun Wang; Huilan Wei (Applied Sciences)
Under the pressure of work and family life, parents face sub-health issues and decreasing communication with their children, while children’s physical and mental health declines due to academic stress. Moderate exercise and companionship could enhance fitness and improve parent–child relationships, driving demand for parent–child interactive fitness facilities. This study aimed to propose a design approach for parent–child interactive exercise bikes. Initially, guided by the flow–clutch state theory, which distinguishes the flow state (highly focused and joyful) from the clutch state (any performance increment or exceptional performance that occurs under pressure), we analyzed user requirements in different psychological states. The theory prioritized design features that promote sustained flow and clutch, ensuring that the product meets the dynamic needs of parents and children. Second, the Analytical Hierarchy Process (AHP) quantified the requirements, Quality Function Deployment (QFD) translated them into functions, and the function–behavior–structure (FBS) model defined the product structures. This study integrates the flow–clutch state theory with AHP-QFD-FBS, proposing a scientific and innovative design approach for the successful design of exercise bikes that meet parent–child needs. The product features novel functions and a rational structure, effectively promoting flow and clutch states to enhance parent–child interaction. This research provides a multi-method design case and practical guidance for parent–child products, benefiting family well-being and relationships.